Medication Reconciliation as Part of Admission Management-A Survey to Improve Drug Therapy Safety in a Urology Department - Yvonne Remane; Luisa Pfeiffer; Leonie Schuhmann; Annett Huke; Jens-Uwe Stolzenburg; Thilo Bertsche (MDPI AG, 2024)
Complete medication reconciliation during hospital admission is the rationale for further treatment decisions. A consecutive, controlled intervention study was conducted to assess discrepancies in medication reconciliation performed by nurses of the Urology Department compared to the Best Possible Medication History (BPMH) established by pharmacists. This study included pre-intervention (control group, CG), nursing training as a pharmaceutical intervention, and post-intervention (intervention group, IG) groups. The discrepancies were classified as "Missing" (not recorded but taken), "Added" (additionally recorded) "Strength" (incorrect documented dosage), "Intake" (incorrect intake time/schedule), "Double" (double prescription), and "Others" (no clear assignment). Additionally, high-risk drug subgroup discrepancies were particularly prevalent and were evaluated. Training success was compared concerning discrepancies in the CG and IG. Generally, the percentage of discrepancies per patient found was lower in the IG than in the CG (78.1% vs. 87.5%, significantly). The category most identified was "Missing" (IG, 33.3% vs. CG, 35.2%). Overall, a discrepancy of 7.4% each (discrepancies: IG, 27 vs. CG, 38) was determined for high-risk drugs while "Missing" occurred (77.8% vs. 52.6%, out of 7.4%). Despite nursing training only partially reducing discrepancies, the implementation of medication reconciliation using BPMH by pharmacists could improve the process, especially for high-risk drugs.